Developments in Current Game-Based Learning Design and Deployment 2012
DOI: 10.4018/978-1-4666-1864-0.ch021
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Strategic Board Games as a Site for Distributed Computational Thinking

Abstract: This paper examines the idea that contemporary strategic board games represent an informal, interactional context in which complex computational thinking takes place. When games are collaborative – that is, a game requires that players work in joint pursuit of a shared goal -- the computational thinking is easily observed as distributed across several participants. This raises the possibility that a focus on such board games are profitable for those who wish to understand computational thinking and learning in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 11 publications
0
45
0
5
Order By: Relevance
“…The instructional approach stems from cognitive and social constructive theories that view learning in a group as a process of actively and collaboratively constructing new knowledge based on prior knowledge and social interaction (Kalaian & Kasim, ). The approach also reflects the notion that cognition can be distributed across a group of people, tools, and artifacts (Berland & Lee, ; Mangalaraj, Nerur, Mahapatra, & Price, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The instructional approach stems from cognitive and social constructive theories that view learning in a group as a process of actively and collaboratively constructing new knowledge based on prior knowledge and social interaction (Kalaian & Kasim, ). The approach also reflects the notion that cognition can be distributed across a group of people, tools, and artifacts (Berland & Lee, ; Mangalaraj, Nerur, Mahapatra, & Price, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These types of activities may also be particularly helpful for students who struggle within traditional classroom formats (Barab & Dede, 2007; Marino et al, 2012). Furthermore, collaborative board games have been shown to engage players in computational thinking (Berland & Lee, 2011), identified as a scientific practice within the NGSS.…”
Section: A Game About Honey Beesmentioning
confidence: 99%
“…Children playing various genres of games have shown a variety of CT patterns employed in their game play [2,7]. A formative study [13] also found that children playing a Connect Four game demonstrate various CTrelated thinking patterns.…”
Section: Computational Thinking and Gamesmentioning
confidence: 99%
“…Learning scientists and education researchers have found that children show a variety of CT skills while playing games [2,7]. However, articulating those tacit skills is a very difficult task for children [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation